The effectiveness of the student teams' achievement divisions in social studies learning on activeness and learning outcomes - Fikri, Asyrul; Saputra, Cheri; Boty, Middya; Rico, Muhammad; Ilmiawan, Ilmiawan; Assidiqi, Muadz; Setiawan, Johan (Intelektual Pustaka Media Utama, 2025)
Student teams’ achievement divisions (STAD) is a learning method that can provide active responses to students so that learning is maximized, but this method is still very rarely used by social studies teachers, thus making social studies learning less than optimal. The purpose of this study is to analyze the effectiveness of the question students have method in social studies learning to increase student activity and learning outcomes. The procedure divides two class groups experimental and control using a quasi-experimental nonequivalent control group design. A sample of 122 seventh-grade kids from a junior high school in Yogyakarta was utilized as the population. While instruments, interviews, and observations were employed in the data collecting process, cluster random sampling was the sampling strategy. An N-gain score test and an independent sample T-test were utilized in the data analysis. The findings demonstrated that, when compared to traditional classroom settings, the STAD's social studies teaching methodology was able to improve student engagement and learning outcomes. The N-gain score test was classified as medium, and the independent sample T-test yielded a significance value of 0.0000.05. Thus, the STAD approach has a huge influence, which makes.